Inflammation and the depot‐specific secretome of human preadipocytes. (10th April 2015) - Zhu, Yi; Tchkonia, Tamara; Stout, Michael B.; Giorgadze, Nino; Wang, Libing; Li, Peter W.; Heppelmann, Carrie J.; Bouloumié, Anne; Jensen, Michael D.; Bergen, H. Robert; Kirkland, James L.
<x xml:space="preserve">Abstract</x> Objective Visceral white adipose tissue (WAT) expansion and macrophage accumulation are associated with metabolic dysfunction. Visceral WAT typically shows greater macrophage infiltration. Preadipocytes show varying proinflammatory expression profiles among WAT depots. The objective was to examine the secretomes and chemoattractive properties of preadipocytes from visceral and subcutaneous WAT. Methods A label‐free quantitative proteomics approach was applied to study secretomes of subcutaneous and omental preadipocytes from obese subjects. Enzyme‐linked immunosorbent assays and chemotaxis assays were used to confirm proinflammatory chemokine secretion between depots. Results Preadipocyte secretomes showed greater variation between depots than did intracellular protein expression. Chemokines were the most differentially secreted proteins. Omental preadipocytes induced chemoattraction of macrophages and monocytes. Neutralizing antibodies to the identified chemokines reduced macrophage/monocyte chemoattraction. Subcutaneous preadipocytes treated with interleukin‐6 (IL‐6) resembled omental preadipocytes in terms of chemokine secretion and macrophage/monocyte chemoattraction. Janus‐activated kinase (JAK1/2) protein expression, which transduces IL‐6 signaling, was higher in omental than subcutaneous preadipocytes and WAT. Inhibiting JAK in omental preadipocytes decreased chemokine secretion and macrophage/monocyte chemoattraction to levels closer to that observed in subcutaneous preadipocytes. Conclusions Secretomes of omental and subcutaneous preadipocytes are distinct, with the former inducing more macrophage/monocyte chemoattraction, in part through IL‐6/JAK‐mediated signaling.